PENGARUH TEMAN SEBAYA DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS DI SMP NEGERI 6 KOTA JAMBI - Redi Indra Yudha (Universitas Batanghari Jambi, 2018)
Abstract The purpose of this research is to know the description and influence of peers and interest in learning on the learning outcomes in IPS subjects of class VII students in SMP Negeri 6 Kota Jambi. The sample in the study amounted to 186 students using proportional random sampling technique from a population of 324 students. Based on the results of research, it can be concluded that the presence of friends who have the same age will cause confidence and the emergence of desire or interest in improving student learning outcomes. Keyword : Peers, Interest in Learning, Learning Outcomes